Detection of Carbapenemases Emerging in Acinetobacter baumannii Clinical Isolates by Modified Hodge Test - Mojtaba Moosavian; Nasim Shams; Mehrandokht Sirous (Pasteur Institute of Iran, 2014)
Introduction: Acinetobacter baumannii, a known causative agent of nosocomial infections, is one of the highly antibiotic-resistant gram-negative bacilli. Carbapenem-resistant Acinetobacter isolates are increasingly reported worldwide. Carbapenems such as imipenem and meropenem are efficient antimicrobial agents commonly used for the treatment of infections caused by multi- resistant A. baumannii strains. Some reports indicate treatment failure due to antibiotic resistant A. baumannii strains. The aim of this study was to determine antibiotic resistance pattern and prevalence carbapenemase production in A. baumannii isolates. Method: A total of 100 A. baumannii isolates were identified from clinical specimens by standard chemical tests. The samples were collected from the patients hospitalized in two teaching hospitals of Ahvaz, southwestern of Iran. The susceptibility of isolates to different antibiotics was determined by the disk diffusion method based on Clinical Laboratory Standards Institute (CLSI) direction. The Modified Hodge Test (MHT) was performed for detection of carbapenemase - producing A. baumannii isolates. Results: The isolates showed the highest resistance to ciprofloxacin (98%). The resistance rate to cefotaxime, ceftazidime, and piperacillin was 97%, gentamicin, amikacin, and meropenem 96%, imipenem 95%, cefepime 93%, and tetracycline 60%. Most of the isolates (99%) were sensitive to colistin. Among the100 A. baumannii isolates, 53 (53%) were positive for carbapenemase production by MHT. Conclusion: This study emphasizes dissemination of carbapenem resistant A. baumannii strains. Our study also showed that the MHT has an excellent sensitivity for detecting carbapenemase - producing A. baumannii isolates.